Assessing the Impact of Structural Reforms Through a Supply-side Framework : The Case of Argentina - Lusinyan, Lusine (Washington, D.C. : International Monetary Fund, 2018)
The paper uses a supply-side framework based on a production function approach to assess the role of structural reforms in boosting long-term GDP growth in Argentina. The impact of product, labor, trade, and tax reforms on each supply-side channel-capital accumulation, labor utilization, and total factor productivity, proxied with an efficiency estimate-is assessed separately and then combined to derive the total impact on growth. The largest effect of structural reforms, involving regulatory changes that promote competition and facilitate flexible forms of employment, comes through the productivity/efficiency channel. Pro-competition regulation also improves labor utilization, while lower entry barriers and trade tariffs are important for capital accumulation. Structural reforms could have substantial effects on Argentina's long-term GDP growth; for example, an ambitious reform effort to improve business regulatory environment would add 1-1 1\2 percent to average annual growth of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet